Cuentas por cobrar del almacén CREDITONSA S.A de Vinces - Lema Paucar, Sonia Esthela (2018)
The present case study has been called: ACCOUNTS RECEIVABLE FROM THE WAREHOUSE CREDITONSA S.A DE VINCES, the warehouse registers its address in the canton Vinces Province of the Rivers located in Cordova avenue and 9 of October, whose activity is the purchase and sale of appliances and white goods, these activities are carried out by means of credits For the present case study is for the purpose of achieving the title of Engineer in Accounting and Auditing, is framed under the research subline of the career indicated as Management of the Accounting Information, which allows in this way to take an understanding relevant to the commercial level of the company, thus making known, the factors to which finds the entity to the breaches of the payments of the credits granted, to the clients to through the sale of appliances, audio and video. The accounts receivable from the CREDITONSA S.A warehouse were taken as reference ensure as the vital asset that the institution has, because it is of paramount importance since the ordinary business of the company is with its normal return and that it achieves have an economic equilibrium in the market. Regarding the non-payment of payment for Some of the clients have established inconveniences and are looking for in the current case study focus on finding out the operations that involve the strategies applied to rescue the credits, executing comparisons between the following years: 2015 and 2016; providing financial information of the CREDITONSA S.A. store, its loan portfolio and knowledge of what are the fictions in the profit of the commercial.